Business Model of a Digital Bank in China's Banking System - Dong Zhang; Yuliana Solovieva (Communications of International Proceedings, 2022)
The global banking sector has undergone significant changes over several years, mostly due to the digitalization of both the environment and business. Today a bank is no longer only a financial services operator, but a platform for doing business. The variety of available technologies allows banking customers to switch to new ways of interacting with each other and with the business. Clients are using more and more channels for obtaining banking services, using new platforms to interact with banks. At the same time, technologies are being adapted to changes in human behavior, as a result of which more and more effective banking solutions are emerging for business development. After 15 years of development, Ant Finance has become one of the most important financial technology platforms in China. In addition to payments, loans, insurance, financial management, credit reports and many other activities, the company has also been engaged in research and development, investment and financial technology discovery for many years. The initial financial cloud has gradually evolved: with the accumulation of many cloud computing capabilities and technical components, it has already surpassed the concept of the traditional financial cloud and includes a whole set of technologies such as computing, big data, AI, IoT, blockchain, etc.
Keywords: digitalization; business model; digital bank; banking services; banking technologies; technologies; online banking.